Natural movement of Belgrade population in the second half of the 20th century and beginning of the 21st century - Tucović Olgica; Stevanović Radoslav (Zbornik Radova: Geografski institut "Jovan Cvijić", 2007)
This paper analyzes the process of natural growth movements of the City of Belgrade in the second half of the 20th and beginning of the 21st centuries. The time level of the analysis was determined by the available data on vital statistics (1961-2005), while the spatial level was determined by the administrative distribution of the City into districts during the 2002 census. It has been established that the natural growth rates for the City of Belgrade were stable until the beginning of the 1980s, though with small oscillations. Then a decrease began until 1992, when the number of deaths exceeded the number of births, with a tendency of negative growth. From then on, the population of Belgrade increased in the last decade of the 20th and beginning of the 21st centuries, only due to the migration component. Although the increase of Belgrade population has never mainly depended on natural growth, it was concluded in the paper that the effects of the ceased natural replacement would yet be shown.